Entrepreneurial Opportunities for Foreign Investors in the Indian Small Industry Sector - A Study Report - Saifil Ali, M. I.; Sristy, Shobha Kiran (Prabandhan: Indian Journal of Management, 2010)
In the current globalised scenario, the strategies (of any country) that formulate programmes for economic development and for the removal of poverty are laying more emphasis on the development of small-scale industrial sector (SSI). The small scale sector in India has emerged as a traditionally vibrant, competitive and dynamic segment of the economy as it provides large scale employment, education and training, capital formation, effective mobilisation of resources, balanced economic growth, expansion of trade, transport and equitable distribution of national income. The SSI gathered momentum along with industrialization and economic growth in India. Being a labor-intensive sector, SSI offers a higher productivity of capital than the capital-intensive sector due to low investment per worker.